2022
DOI: 10.1371/journal.pone.0267356
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of human olfactory receptors with a high basal activity using LNCaP cell line

Abstract: Humans use a family of more than 400 olfactory receptors (ORs) to detect odorants. However, deorphanization of ORs is a critical issue because the functional properties of more than 80% of ORs remain unknown, thus, hampering our understanding of the relationship between receptor function and perception. HEK293 cells are the most commonly used heterologous expression system to determine the function of a given OR; however, they cannot functionally express a majority of ORs probably due to a lack of factor(s) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Our finding that acetophenone attracts wild-type C. elegans and repels tax-4 mutants (Figs 6, 7) implies that there are also at least two acetophenone receptors in C. elegans. Three of these plant SMs, anisole, camphor, and cinnamyl alcohol, also activate human olfactory GPCRs [88][89][90]. The weak repellents, ellagic acid and methyl palmitate, activate human GPR35 and the CB1/2 receptors [91,92], respectively, and oleanolic acid and ursolic acid both activate GPBAR1 [93,94].…”
Section: Several Plant Sms Detected By C Elegans Are Ligands For Huma...mentioning
confidence: 99%
“…Our finding that acetophenone attracts wild-type C. elegans and repels tax-4 mutants (Figs 6, 7) implies that there are also at least two acetophenone receptors in C. elegans. Three of these plant SMs, anisole, camphor, and cinnamyl alcohol, also activate human olfactory GPCRs [88][89][90]. The weak repellents, ellagic acid and methyl palmitate, activate human GPR35 and the CB1/2 receptors [91,92], respectively, and oleanolic acid and ursolic acid both activate GPBAR1 [93,94].…”
Section: Several Plant Sms Detected By C Elegans Are Ligands For Huma...mentioning
confidence: 99%
“… 80 More recently, the ability of ORs to functionally express ectopically has led to the use of human prostate carcinoma to generate OR-based sensors. 81 …”
Section: Olfactory Receptor-based Sensorsmentioning
confidence: 99%
“…Alternative cell lines include HeLA/Olf, where cAMP increases results in a Ca 2+ influx that can be measure via fluorescence . More recently, the ability of ORs to functionally express ectopically has led to the use of human prostate carcinoma to generate OR-based sensors …”
Section: Olfactory Receptor-based Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence information of human ORs used in this study was reported previously 10,40 . Genes coding human ORs, trace amine-associated receptors (TAARs), and vomeronasal receptors type I (VN1R1s) were ampli ed from human genomic DNA (Promega, Madison, WI, USA).…”
Section: Expression Vectormentioning
confidence: 99%